The Civil Rights of an Individual in a Certificate of Inheritance Proven to Have Been Based on Forged Documents - Candrika Arivia Apriliani; Rachmi Sulistyarini; M. Sudirman (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study aims to analyze the civil rights of lawful heirs affected by a Certificate of Inheritance Rights proven to have been issued on the basis of forged documents and to examine the forms of civil liability arising from such unlawful conduct. This research employs a normative legal research method using both statutory and case approaches through the examination of legislation, legal doctrines, and the Supreme Court Decision Number 1470 K/Pid/2023. The findings demonstrate that document forgery in the preparation of a Certificate of Inheritance Rights gives rise to legal consequences in the form of the loss of inheritance rights, loss of recognition as a legal subject within inheritance relations, and deprivation of the right to control and enjoy the deceased’s estate. Such conduct constitutes an unlawful act that contravenes the principles of legal protection and legal certainty. Civil liability toward the aggrieved lawful heirs is based on Article 1365 of the Indonesian Civil Code through the provision of compensation, the annulment of the legally defective Certificate of Inheritance, and the restoration of the original legal condition through the reinstatement of the lawful heirs’ legal status. The novelty of this research lies in its focus on the restoration of heirs’ civil rights resulting from the forgery of a Certificate of Inheritance from the perspective of legal protection and victims’ rights recovery.